Loss of At4 function impacts phosphate distribution between the roots and the shoots during phosphate starvation - Shin, Heungsop; Shin, Hwa‐Soo; Chen, Rujin; Harrison, Maria J. (The Plant journal : for cell and molecular biology, 2006)
Summary Plants display a range of adaptive responses to phosphate (Pi) starvation including an increase in the proportion of Pi allocated to the roots, which enhances lateral root development and consequently Pi acquisition. The mechanisms by which plants sense Pi and signal Pi reallocation are largely unknown. Previously, we cloned At4, a gene predicted to contain multiple short open‐reading frames (ORFs), whose expression is strongly induced by Pi starvation. At4 is a member of a small gene family whose members, AtIPS1 and two additional genes reported here, At4.1 and At4.2, share little conservation among the predicted ORFs but high conservation of a 22‐nt sequence located in the 3′ half of the transcript. Here, we show that under Pi‐starvation conditions, At4 is expressed in the vascular tissue and transcript levels are regulated by both cytokinin and ABA. at4, an At4 loss‐of‐function mutant fails to redistribute Pi to the roots correctly in response to Pi deprivation and At4 shoots continue to accumulate a greater proportion of Pi relative to wild type. Consistent with this, the primary root growth rate in at4 is faster than wild type in low‐Pi conditions. The conserved sequence found in all members of the At4 gene family hybridizes to a small RNA present in Pi‐starved roots. These data support a role for At4 in the internal allocation of Pi and suggest that the At4 gene is not only subject to Pi‐starvation‐inducible expression, but that transcript levels may be adjusted at a post‐transcriptional level by the activity of an miRNA.